Decolonizing the metropolis: crisis and renewal - Becker-Topkara, Elisabeth; Everett, Samuel Sami (Patterns of prejudice, 2023)
Debates over borders and belonging in the post-imperial age have focused on the nation-state, with identifications and rights situated in a national sphere of citizenship. The unsettledness of contemporary European societies that has developed not only against, but also through colonial and imperial endeavours reveals the incapacity of national framings to fully make sense of plurality, including both the structural constraints on and the agency of minoritized populations in Europe. In this introduction to the special issue, Decolonizing the Metropolis: Crisis and Renewal, the editors Becker and Everett turn to the level of the metropolis in order to investigate contestations over belonging in Germany, France and the United Kingdom. During colonial and imperial endeavours, 'metropolis' was used to signal the economic core of empire. Here they instead invoke the post-imperial metropolis as the cultural core, in which lived experiences, including conflicts and solidarities, are negotiated by urban denizens who strive to transcend the failures of the nation-state to foster belonging. The twenty-first-century European city emerges as a place both of enclosure and openness, de-and re-racialization: a site of renewal amidst parallel crises of cohesion, coherence and democracy.
Introduction
Gesehen am 23.04.2024